1662. The Prevalence of M. tuberculosis among Acid Fast Cultures from Military Health System Beneficiaries from Hawaii and Pacific Islands from January 2002 to November 2019. (31st December 2020) - Crecelius, Elena M; Lustik, Michael; Horseman, Timothy; Jones, Milissa
Abstract: Background: Tuberculosis (TB), caused by Mycobacterium tuberculosis (MTB), is the leading infectious cause of death worldwide and the state of Hawaii (HI) has the second highest case rate of TB in the United States. The prevalence of TB among military health system (MHS) beneficiaries (active duty service members, retirees, dependents, civilians and eligible Pacific Island civilians) in HI has not been previously reported. Our analysis evaluates the prevalence of MTB among acid fast cultures (AFCs) tested at Tripler Army Medical Center (TAMC) on Oahu, HI and describes demographic factors associated with positive samples. Methods: We analyzed AFC results from TAMC clinical diagnostic microbiology laboratory from January 2002 to November 2019. Demographic data were recorded for each individual with an AFC sample during the study period. Prevalence was calculated based on the number of MTB-positive AFCs per all AFCs over the study period. Multivariable logistic regression was used to evaluate associations between demographic factors and MTB-positive AFC results. Results: From January 2002 to November 2019 there were 4768 AFCs resulted at TAMC with 49 MTB-positive AFC, leading to a cumulative prevalence of 1.03 percent (Figure 1). After controlling for other factors, Asian-Pacific Islanders had nearly 15 times higher odds of having a positive AFC than whites (OR=14.96, 95% CI 5.03, 44.55, p=< 0.001) and active duty personnel had 2.6 times the odds of having a positive AFC than dependents, civilians and retirees (OR=2.6, 95% CI 0.94, 7.22, p=0.067). Figure 1. The Prevalence of M. tuberculosis (MTB) among Acid Fast Cultures (AFC) from Military Health System Beneficiaries from Hawaii and Pacific Islands from January 2002 to November 2019. Conclusion: The low prevalence of MTB among AFCs performed at our institution over nearly 16 years suggests that living in the state of HI does not appear to confer high rates of TB to MHS beneficiaries. Persons with Asian-Pacific Islander ethnicity have higher odds of positive AFC which corroborates prior studies regarding risk factors for MTB. Further analysis is needed to further define risk factors associated with positive AFC among MHS beneficiaries in HI. Follow-up analysis is underway to describe the clinical course of the persons with MTB-positive AFC from this study. Disclosures: All Authors : No reported disclosures